العوامل المحددة للهيكل المالي في المؤسسات الخدماتية المدرجة في سوق الخرطوم للأوراق المالية خلال الفترة 2014-2016 - حفصي, رشيد; دادن, عبد الغفور; نعاس, صلاح الدين (University of Eloued جامعة الوادي, 2018)
تهدف هذه الدراسة إلى إستخراج العوامل المحددة للهيكل المالي في مؤسسات الخدمية المدرجة في بورصة الخرطوم للأوراق المالية خلال الفترة 2014-2016 من خلال إستخدام نموذج الإنحدار الذاتي المتعدد للبيانات الطولية (Panal) وبالإستعانة ببرنامج Eviews 09 لتفسير وإيجاد العلاقة بين هيكل المالي ومجموعة من المتغيرات المالية والممثلة في: هيكل الأصول، حجم المؤسسة، عمر المؤسسة، معدل النمو ومعدل المردودية المالية وعائد على الأصول وشملت العينة 30 مؤسسة خدمية. وقد توصلت الدراسة إلى أن كل من عائد على الأصول وحجم المؤسسة والمردودية المالية هما المحددات الأكثر تأثيرا في تفسير الهيكل المالي لهذه المؤسسات، في حين أن كل من هيكل الأصول، معدل النمو وعمر المؤسسة ليس لها دلالة إحصائية وبالتالي لا تلعب أي دور في تفسير الهيكل المالي لهذه المؤسسات الخدمات المدرجة في البورصة. Abstract: The main objective of the study was to extract the specific factors of the financial structure in the services sector in the Khartoum Stock Exchange during the period 2014-2016 through the use of the Panal longitudinal regression model and using the Eviews 09 program used to explain and find the relationship between the financial structure and a range of financial and representative variables In: asset structure, size of the institution, age of the institution, growth rate, financial rate of return and return on assets. The sample included 30 service establishments. The study found that the return on assets, size of the institution and financial profitability were the most influential determinants of the financial structure of these institutions, while the asset structure, growth rate and the age of the institution had no statistical significance and thus play no role in interpreting the financial structure For these institutions.
determining Factors to the financial structure of service companies listed on the Khartoum Stock Exchange during the period 2014-2016
مجلة رؤى المجلد الثامن العدد الأول
Keywords: G32 :JEL ت محددات الهيكل المالي، الهيكل المالي، مؤسسة خدمية، بورصة الخرطوم،; Determinants of Financial Structure; Financing; Financial Structure; Service Establishment; Khartoum Stock Exchange. Jel Classification Codes : G32.